Where in the World are you? Assessing the Importance of Circumstance and Effort in a World of Different Mean Country Incomes and (Almost) No Migration - Milanovic, Branko (World Bank, Washington, DC, 2012)
Suppose that all people in the world are allocated only two characteristics: country where they live and income class within that country. Assume further that there is no migration. This paper shows that 90 percent of variability in people's global income position (percentile in world income distribution) is explained by only these two pieces of information. Mean country income (circumstance) explains 60 percent, and income class (both circumstance and effort) 30 percent of global income position. The author finds that about two-thirds of the latter number is due to circumstance (approximated by the estimated parental income class under various social mobility assumptions), which makes the overall share of circumstance unlikely to be less than 75-80 percent. On average, "drawing" one-notch higher income class (on a twenty-class scale) is equivalent to living in a 12 percent richer country. Once people are allocated their income class, it becomes important, not only whether the country they are allocated to is rich or poor, but whether it is egalitarian or not. This is particularly important for the people who "draw" low or high classes; for the middle classes, the country's income distribution is much less important than mean country income.